Leaving Emotion Out - Bridgette Toy-Cronin (Oñati Socio-Legal Series)
Litigants in person (LiPs) receive the message that emotion should be “left out” of New Zealand courtrooms. This is a confusing and impossible goal. This paper draws on two empirical studies and argues that the exhortation to leave emotion out is multi-layered, referring to behaving and thinking like a lawyer, including a focus on the commercial or transactional elements of disputes, rather than on other aspects that are important to litigants. This is often not possible for LiPs and it can reduce their sense of procedural justice and result in the omission of legally relevant material. Judges can respond to LiPs who violate the emotion regime by allowing LiPs to explain aspects of the dispute that are salient to them. We need to consider how the civil courts can allow more space for litigants to tell stories, rather than focusing only on the commercial or transactional aspects of disputes.